Graphic organizers as teaching tools - Montaño, Rosario Y. (Danyag :the UPV journal of humanities and social sciences)
"State-of-the-art instructional tools, which are almost within reach of teachers, have contributed much to the improvement of the teaching-learning process. However, unfamiliarity with these tools and other constraints sometimes prevent teachers from using these modern instruments. But teachers need not despair because there are alternative ways which can be just as effective and can make the classroom as alive and interactive. One such way is the use of graphic organizers (GO's). GO's are reliable tools for achieving the goals of most lessons. To address concerns of details related to this alternative teaching tool, this article focuses on the definition and nature of graphic organizers and their importance in the teaching-learning process. It also: (1) examines the five main types of graphic organizers; (2) identifies the critical thinking skills that they enhance; and (3) offers some guidelines in designing GO's and strategies on how teachers can assist students in making their own format according to their interest and capabilities. It finally provides examples for each type of GO to guide the teachers to make their own."